A metallization process for high voltage DC relay ceramics
By performing porous treatment and multi-step sintering process on the ceramic surface, the problem of insufficient bonding strength between the molybdenum manganese metallization layer and the ceramic is solved, and the vacuum air tightness and current bearing capacity of the high-voltage DC relay ceramics are significantly improved, achieving more stable metallization effect.
Patent Information
- Application Number
- CN202410050347.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-01-12
AI Technical Summary
In the metallization process of existing high-voltage DC relay ceramics, the bonding strength between the molybdenum manganese metallization layer and the ceramic surface is insufficient, resulting in poor vacuum air tightness and current bearing capacity, which is difficult to meet the needs of electronic control technology of new energy vehicles.
By porous treatment on the ceramic surface, a porous ceramic sheet is prepared and a metallization paste is prepared on it. The bonding strength of the metallization layer and the ceramic is enhanced by a multi-step sintering process, including alumina foaming paste and impregnation. Preparation of slurry sponges, preparation of porous ceramic sheets on the surface, preparation of metallization paste, and coarse and metallization process.
The bonding strength and airtightness of the metallized layer and ceramics are significantly improved, the vacuum sealing strength and current carrying capacity of the relay are enhanced, the loss is reduced, and the stability of metallized high-voltage DC relay ceramics is improved.
Smart Images

Figure CN118005382B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic metallization processing, in particular to a metallization process for high-voltage direct current relay ceramics. Background Art
[0002] High-voltage DC relays are the core components of new energy vehicle electronic control technology. It is often necessary to vacuum seal the relay ceramics, seal the contact points of the relays and isolate them from the outside air to obtain high-voltage relays. The key to vacuum sealing relay ceramics is to metallize the ceramics. By preparing a dense and tightly connected molybdenum-manganese metallization layer on the ceramic surface, the sealing ability of the ceramics and other metal parts is improved, thereby ensuring the vacuum tightness of the relay.
[0003] The preparation of molybdenum-manganese metallization layer usually involves preparing metallization slurry with molybdenum, manganese and various oxides, and then applying the metallization slurry on the ceramic surface through various coating processes, and then sintering to obtain metallized ceramics. This method can theoretically achieve the purpose of adding various oxides to make the metallization layer closely connected to the ceramic surface, but in actual operation, due to the excessive dispersion of various components, it is difficult to give full play to the role of various oxides, so that the metallization effect of the ceramic does not achieve the expected effect and is too limited.
[0004] In order to solve the above-mentioned process difficulties, the present invention provides a metallization process for high-voltage DC relay ceramics, which greatly improves the bonding strength between the metallization layer and the ceramic by making the ceramic surface porous, thereby improving the airtightness of the ceramic. Summary of the invention
[0005] In order to solve the above technical defects, the present invention provides a metallization process for high-voltage DC relay ceramics, which greatly improves the bonding strength between the metallization layer and the ceramic by making the ceramic surface porous, thereby improving the airtightness of the ceramic.
[0006] A metallization process for high voltage DC relay ceramics comprises the following steps:
[0007] S1: Preparation of alumina foaming slurry and impregnated sponge;
[0008] S2: Preparation of ceramic sheets with porous surfaces;
[0009] S3: Preparation of metallization paste;
[0010] S4: Roughening and metallization of porous ceramic sheets.
[0011] Furthermore, step S1 of preparing alumina foamed slurry and impregnated sponge comprises the following steps:
[0012] S1.1: 18-20 parts of aluminum oxide, 0.4-0.5 parts of silicon oxide, 0.4-0.5 parts of magnesium oxide, 0.2-0.3 parts of calcium oxide and 0.3-0.4 parts of titanium oxide are placed in a ball mill of a planetary ball mill, 6-8 parts of anhydrous ethanol are added, the ball mill speed is adjusted to 260-280 rpm, and the ball mill is performed for 5-6 hours to obtain a ball milled material;
[0013] S1.2: Take 2-3 parts of ball-milled materials and place them in a container, add 0.02-0.03 parts of carboxymethyl cellulose and 0.008-0.01 parts of polyacrylamide, and then add 0.5-0.6 parts of glass powder and 0.3-0.4 parts of deionized water, stir to prepare alumina foaming slurry, immerse a polyurethane sponge with a thickness of 0.5-0.6 cm in the alumina foaming slurry, stir to make it completely immersed, and obtain a slurry-impregnated sponge for use.
[0014] Furthermore, step S2 of preparing a ceramic sheet with a porous surface comprises the following steps:
[0015] S2.1: Take 16-17 portions of the ball-milled material obtained in step S1.1, place them in a drying oven at 70-75°C for 2-3 hours, then place them in a grinder for grinding and granulation, and then press them into green bodies by cold isostatic pressing to obtain ceramic green bodies;
[0016] S2.2: Remove excess slurry from the impregnated sponge by centrifugation and rolling, and then tightly wrap it on the surface of the ceramic blank and fix it to obtain a ceramic wrapped blank. Put the ceramic wrapped blank into an oven and dry it at 80-85℃ for 2-3 hours, then put it into a gas pressure sintering furnace, introduce nitrogen to make the pressure in the kettle reach 0.5-0.6Mpa, heat it to 180-200℃ at a heating rate of 5-6℃ / min, then heat it to 600-650℃ at a rate of 2-3℃ / min, keep it warm for 50-55 minutes, and finally heat it to 1500-1600℃ at 10-12℃, keep it warm for 2-3 hours, and then cool it down to room temperature naturally to obtain a ceramic sheet with a porous surface.
[0017] Furthermore, the preparation of the metallization paste in step S3 includes the following steps:
[0018] S3.1: 1-2 parts of aluminum oxide, 6-8 parts of molybdenum, 2-3 parts of manganese, 1-2 parts of silicon oxide, 0.2-0.3 parts of lithium oxide, 2-3 parts of yttrium oxide powder and 4-5 parts of anhydrous ethanol are mixed and added into a planetary ball mill, the ball milling speed is adjusted to 180-200 rpm, and the ball milling is performed for 3-4 hours to obtain a mixture;
[0019] S3.2: Dry the mixture in an oven at 75-80°C for 2-3 hours, add adhesive after natural cooling, and mix well to obtain a metallization paste.
[0020] Furthermore, step S4 of roughening and metallizing the porous ceramic sheet comprises the following steps:
[0021] S4.1: Immerse the ceramic sheet with a porous surface in a sodium hydroxide solution with a concentration of 1.2-1.25 mol / L, heat it in a constant temperature water bath at 50-55°C for 8-10 minutes, rinse it with distilled water 2-3 times, and then immerse it in an acid washing solution, heat it in a constant temperature water bath at 50-55°C for 45-60 minutes, take it out and rinse it with distilled water 2-3 times to obtain a roughened ceramic sheet;
[0022] S4.2: Take 1 / 2-2 / 3 of the metallization paste and apply it evenly on the surface of the roughened ceramic sheet by screen printing, then place it in a vacuum sintering furnace and adjust the vacuum degree to 1×10 -3 -5×10 -3 Pa, sintered at 1500-1600℃ for 1-2 hours to obtain a primary sintered ceramic sheet, the remaining metallization paste was evenly coated on the surface of the primary sintered ceramic sheet by silk screen printing, and then placed in a vacuum sintering furnace, and the vacuum degree was adjusted to 1×10 -3 -5×10 -3 Pa, sintered at a temperature of 800-900°C for 2-3 hours, and naturally cooled to room temperature to obtain a metallized high voltage DC relay ceramic.
[0023] Furthermore, the composition of the glass powder in step S1.2 and the mass fraction of each component are: SiO2: 98-99%, Al2O3: 0.5-1.5%, Fe2O3: 0.05-0.1%, CaO: 0.1-0.5%, MgO: 0.1-0.5%.
[0024] Furthermore, in step S1.2, the pore number of the polyurethane sponge is 45-50 ppi.
[0025] Furthermore, the particle size of the grinding granulation in step S2.1 is 10-15 μm.
[0026] Furthermore, the adhesive in step S3.2 is prepared from ethyl cellulose and pinene alcohol in a mass ratio of 1:(25-28).
[0027] Furthermore, the components of the pickling solution in step S4.1 are: 100-120 mL / L of sulfuric acid and 1.8-2 mol / L of CrO3.
[0028] The beneficial effects are as follows: 1. The present invention prepares a slurry-impregnated sponge, wraps it around and fixes it on the surface of a ceramic blank, and then dries and sinters it under air pressure. The polyurethane sponge evaporates and is removed during the staged heating sintering process, leaving a porous foam ceramic. The foam ceramic has a similar composition to the ceramic blank and has similar wettability. Under the action of sintering and infiltration, the foam ceramic cooperates with the bonding of glass powder to form a layer of tightly connected porous ceramic bodies on the surface of the ceramic blank, thereby obtaining a ceramic sheet with a porous surface. In the subsequent metallization process, the contact area between the foam ceramic and the metal slurry is greatly increased. The bonding strength of the metallization layer after sintering can be greatly improved without relying on the composition of the metal slurry, thereby ensuring the vacuum sealing strength and air tightness of the metallized high-voltage DC relay ceramic. When it is prepared into a relay, its current carrying capacity is enhanced and more stable, thereby reducing losses.
[0029] 2. The present invention cleans and roughens the porous ceramic sheet by immersing the porous ceramic sheet in a sodium hydroxide solution and a pickling solution in a constant temperature water bath, and then applies a metallizing paste on the surface of the roughened ceramic sheet, thereby enhancing the wetting effect of the metallizing paste on the roughened ceramic sheet during the sintering process, further enhancing the bonding strength of the metallizing layer of the metallized high-voltage DC relay ceramic, and improving the stability of the metallized high-voltage DC relay ceramic.
[0030] 3. The present invention adds lithium oxide and yttrium oxide to the metallization paste. The low-melting-point lithium oxide can promote the mutual migration of molybdenum and ceramic phases and improve the peeling strength of the metallization layer, while the high-melting-point yttrium oxide can fill the pores generated during the sintering process, making the metallization layer denser and improving the stability of the metallized high-voltage DC relay ceramic during sealing. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A process flow chart of metallization of high voltage DC relay ceramics used in an embodiment of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0033] A metallization process for high voltage DC relay ceramics, such as Figure 1 As shown, the following steps are included:
[0034] S1: Preparation of alumina foaming slurry and impregnated sponge
[0035] S1.1: 18 parts of aluminum oxide, 0.4 parts of silicon oxide, 0.4 parts of magnesium oxide, 0.2 parts of calcium oxide and 0.3 parts of titanium oxide are placed in a ball mill of a planetary ball mill, 6 parts of anhydrous ethanol are added, the ball mill speed is adjusted to 260 rpm, and the ball mill is milled for 5 hours to obtain a ball milled material;
[0036] S1.2: Take 2 parts of ball-milled materials and place them in a container, add 0.02 parts of carboxymethyl cellulose and 0.008 parts of polyacrylamide, and then add 0.5 parts of glass powder and 0.3 parts of deionized water, wherein the composition of the glass powder and the mass fraction of each component are: SiO2: 98%, Al2O3: 1%, Fe2O3: 0.1%, CaO: 0.5%, MgO: 0.4%, stir to prepare alumina foaming slurry, immerse a polyurethane sponge with a thickness of 0.5 cm and a pore number of 45 ppi in the alumina foaming slurry, stir to make it completely immersed, and obtain the impregnated sponge for use.
[0037] S2: Preparation of porous ceramic sheets
[0038] S2.1: 16 portions of the ball-milled material obtained in step S1.1 are placed in a drying oven and dried at 70°C for 2 hours, then placed in a grinder for grinding and granulation, the particle size of the ground granulation is 10 μm, and then pressed by cold isostatic pressing to obtain a ceramic blank;
[0039] S2.2: Remove excess slurry from the impregnated sponge by centrifugation and rolling, then tightly wrap it on the surface of the ceramic blank and fix it to obtain a ceramic wrapped blank. Put the ceramic wrapped blank into an oven and dry it at 80°C for 2 hours, then put it into a gas pressure sintering furnace, introduce nitrogen to make the pressure in the kettle reach 0.5Mpa, heat it to 180°C at a heating rate of 5°C / min, then heat it to 600°C at a rate of 2°C / min, keep it warm for 50 minutes, and finally heat it to 1500°C at 10°C, keep it warm for 2 hours, and then naturally cool it to room temperature. The polyurethane sponge is volatilized and removed during the staged heating sintering process, leaving The porous foam ceramic is similar to the ceramic blank in composition and has similar wettability. Under the action of sintering and infiltration, the foam ceramic cooperates with the bonding of glass powder to form a layer of tightly connected porous ceramic body on the surface of the ceramic blank to obtain a ceramic sheet with a porous surface. In the subsequent metallization process, the contact area between the foam ceramic and the metal slurry is greatly increased. The peel strength of the metallized layer after sintering can be greatly improved without relying on the composition of the metal slurry, thereby ensuring the vacuum sealing strength and airtightness of the metallized high-voltage DC relay ceramic. When it is prepared into a relay, its current carrying capacity is enhanced and more stable, thereby reducing losses.
[0040] S3: Preparation of metallization paste
[0041] S3.1: 1 part of aluminum oxide, 6 parts of molybdenum, 2 parts of manganese, 1 part of silicon oxide, 0.2 parts of lithium oxide, 2 parts of yttrium oxide powder and 4 parts of anhydrous ethanol are mixed and added into a planetary ball mill, and the ball milling speed is adjusted to 180 rpm. The ball milling is performed for 3 hours to obtain a mixture. The low-melting-point lithium oxide can promote the mutual migration of molybdenum and ceramic phases and improve the peeling strength of the metallization layer, while the high-melting-point yttrium oxide can fill the pores generated during the sintering process, making the metallization layer denser and improving the stability of the metallized high-voltage DC relay ceramic during sealing;
[0042] S3.2: The mixture is placed in an oven and dried at 75°C for 2 hours. After natural cooling, an adhesive is added. The adhesive is prepared by mixing ethyl cellulose and pinene alcohol in a mass ratio of 1:25. The mixture is evenly mixed to obtain a metallization paste.
[0043] S4: Roughening and metallization of porous ceramic sheets
[0044] S4.1: Immerse the ceramic sheet with a porous surface in a sodium hydroxide solution with a concentration of 1.2 mol / L, heat it in a constant temperature water bath at 50°C for 8 minutes, rinse it with distilled water twice, and then immerse it in a pickling solution with a concentration of 100 mL / L, the components of the pickling solution are: 100 mL / L sulfuric acid and 1.8 mol / L CrO3, heat it in a constant temperature water bath at 50°C for 45 minutes, take it out and rinse it with distilled water twice, clean and roughen the ceramic sheet with a porous surface, enhance the subsequent metallization paste infiltration effect with the roughened ceramic sheet during the sintering process, further enhance the peel strength of the metallization layer of the metallized high-voltage DC relay ceramic, and improve the stability of the metallized high-voltage DC relay ceramic to obtain a roughened ceramic sheet;
[0045] S4.2: Take 1 / 2 of the metallization paste and apply it evenly on the surface of the roughened ceramic sheet by screen printing, then place it in a vacuum sintering furnace and adjust the vacuum degree to 1×10 -3 Pa, sintered at 1500 °C for 1.5 hours to obtain a primary sintered ceramic sheet, the remaining metallization paste was evenly coated on the surface of the primary sintered ceramic sheet by screen printing, and then placed in a vacuum sintering furnace and the vacuum degree was adjusted to 1×10 -3 Pa, sintered at 800°C for 2 hours, and naturally cooled to room temperature to obtain a metallized high voltage DC relay ceramic. Example 2
[0046] A metallization process for high voltage DC relay ceramics, such as Figure 1 As shown, the following steps are included:
[0047] S1: Preparation of alumina foaming slurry and impregnated sponge
[0048] S1.1: 20 parts of aluminum oxide, 0.5 parts of silicon oxide, 0.5 parts of magnesium oxide, 0.3 parts of calcium oxide and 0.4 parts of titanium oxide are placed in a ball mill of a planetary ball mill, 8 parts of anhydrous ethanol are added, the ball mill speed is adjusted to 260 rpm, and the ball mill is performed for 5 hours to obtain a ball milled material;
[0049] S1.2: Take 3 parts of ball-milled materials and place them in a container, add 0.03 parts of carboxymethyl cellulose and 0.01 parts of polyacrylamide, and then add 0.6 parts of glass powder and 0.4 parts of deionized water, wherein the composition of the glass powder and the mass fraction of each component are: SiO2: 99%, Al2O3: 0.5%, Fe2O3: 0.1%, CaO: 0.2%, MgO: 0.2%, stir to prepare alumina foaming slurry, immerse a polyurethane sponge with a thickness of 0.5 cm and a pore number of 45 ppi in the alumina foaming slurry, stir to make it completely immersed, and obtain the impregnated sponge for use.
[0050] S2: Preparation of porous ceramic sheets
[0051] S2.1: 17 portions of the ball-milled material obtained in step S1.1 are placed in a drying oven and dried at 70°C for 2 hours, then placed in a grinder for grinding and granulation, the particle size of the ground granulation is 10 μm, and then pressed by cold isostatic pressing to obtain a ceramic blank;
[0052] S2.2: Remove excess slurry from the impregnated sponge by centrifugation and rolling, then tightly wrap it on the surface of the ceramic blank and fix it to obtain a ceramic wrapped blank. Put the ceramic wrapped blank into an oven and dry it at 80°C for 2 hours, then put it into a gas pressure sintering furnace, introduce nitrogen to make the pressure in the kettle reach 0.5Mpa, heat it to 180°C at a heating rate of 5°C / min, then heat it to 600°C at a rate of 2°C / min, keep it warm for 50 minutes, and finally heat it to 1500°C at 10°C, keep it warm for 2 hours, and then naturally cool it to room temperature. The polyurethane sponge is volatilized and removed during the staged heating sintering process, leaving The porous foam ceramic is similar to the ceramic blank in composition and has similar wettability. Under the action of sintering and infiltration, the foam ceramic cooperates with the bonding of glass powder to form a layer of tightly connected porous ceramic body on the surface of the ceramic blank to obtain a ceramic sheet with a porous surface. In the subsequent metallization process, the contact area between the foam ceramic and the metal slurry is greatly increased. The peel strength of the metallized layer after sintering can be greatly improved without relying on the composition of the metal slurry, thereby ensuring the vacuum sealing strength and airtightness of the metallized high-voltage DC relay ceramic. When it is prepared into a relay, its current carrying capacity is enhanced and more stable, thereby reducing losses.
[0053] S3: Preparation of metallization paste
[0054] S3.1: 2 parts of aluminum oxide, 8 parts of molybdenum, 3 parts of manganese, 2 parts of silicon oxide, 0.3 parts of lithium oxide, 3 parts of yttrium oxide powder and 5 parts of anhydrous ethanol are mixed and added into a planetary ball mill, and the ball milling speed is adjusted to 180 rpm. The ball milling is performed for 3 hours to obtain a mixture. The low-melting-point lithium oxide can promote the mutual migration of molybdenum and ceramic phases and improve the peeling strength of the metallization layer, while the high-melting-point yttrium oxide can fill the pores generated during the sintering process, making the metallization layer denser and improving the stability of the metallized high-voltage DC relay ceramic during sealing;
[0055] S3.2: The mixture is placed in an oven and dried at 75°C for 2 hours. After natural cooling, an adhesive is added. The adhesive is prepared by mixing ethyl cellulose and pinene alcohol in a mass ratio of 1:28. The mixture is mixed evenly to obtain a metallization paste.
[0056] S4: Roughening and metallization of porous ceramic sheets
[0057] S4.1: Immerse the ceramic sheet with a porous surface in a sodium hydroxide solution with a concentration of 1.2 mol / L, heat it in a constant temperature water bath at 50°C for 8 minutes, rinse it with distilled water twice, and then immerse it in a pickling solution with a concentration of 100 mL / L, the components of the pickling solution are: 100 mL / L sulfuric acid and 1.8 mol / L CrO3, heat it in a constant temperature water bath at 50°C for 45 minutes, take it out and rinse it with distilled water twice, clean and roughen the ceramic sheet with a porous surface, enhance the subsequent metallization paste infiltration effect with the roughened ceramic sheet during the sintering process, further enhance the peel strength of the metallization layer of the metallized high-voltage DC relay ceramic, and improve the stability of the metallized high-voltage DC relay ceramic to obtain a roughened ceramic sheet;
[0058] S4.2: Take 2 / 3 of the metallization paste and apply it evenly on the surface of the roughened ceramic sheet by screen printing, then place it in a vacuum sintering furnace and adjust the vacuum degree to 1×10 -3 Pa, sintered at 1500 °C for 1.5 hours to obtain a primary sintered ceramic sheet, the remaining metallization paste was evenly coated on the surface of the primary sintered ceramic sheet by screen printing, and then placed in a vacuum sintering furnace and the vacuum degree was adjusted to 1×10 -3 Pa, sintered at 800°C for 2 hours, and naturally cooled to room temperature to obtain a metallized high voltage DC relay ceramic. Example 3
[0059] A metallization process for high voltage DC relay ceramics, such as Figure 1 As shown, the following steps are included:
[0060] S1: Preparation of alumina foaming slurry and impregnated sponge
[0061] S1.1: 18 parts of aluminum oxide, 0.4 parts of silicon oxide, 0.4 parts of magnesium oxide, 0.2 parts of calcium oxide and 0.3 parts of titanium oxide are placed in a ball mill of a planetary ball mill, 6 parts of anhydrous ethanol are added, the ball mill speed is adjusted to 280 rpm, and the ball mill is performed for 6 hours to obtain a ball milled material;
[0062] S1.2: Take 2 parts of ball-milled materials and place them in a container, add 0.02 parts of carboxymethyl cellulose and 0.008 parts of polyacrylamide, and then add 0.5 parts of glass powder and 0.3 parts of deionized water, wherein the composition of the glass powder and the mass fraction of each component are: SiO2: 98%, Al2O3: 1%, Fe2O3: 0.1%, CaO: 0.5%, MgO: 0.4%, stir to prepare alumina foaming slurry, immerse a polyurethane sponge with a thickness of 0.6 cm and a pore number of 50 ppi in the alumina foaming slurry, stir to make it completely immersed, and obtain the impregnated sponge for use.
[0063] S2: Preparation of porous ceramic sheets
[0064] S2.1: 16 portions of the ball-milled material obtained in step S1.1 are placed in a drying oven and dried at 75°C for 3 hours, then placed in a grinder for grinding and granulation, the particle size of the ground granulation is 15 μm, and then pressed by cold isostatic pressing to obtain a ceramic blank;
[0065] S2.2: Remove excess slurry from the impregnated sponge by centrifugation and rolling, then wrap it tightly on the surface of the ceramic blank and fix it to obtain a ceramic wrapped blank. Put the ceramic wrapped blank into an oven and dry it at 85°C for 3 hours, then put it into a gas pressure sintering furnace, introduce nitrogen to make the pressure in the kettle reach 0.3Mpa, heat it to 200°C at a heating rate of 6°C / min, then heat it to 650°C at a rate of 3°C / min, keep it warm for 55 minutes, and finally heat it to 1600°C at 12°C. After keeping it warm for 3 hours, naturally cool it to room temperature. The polyurethane sponge is volatilized and removed during the staged heating sintering process, leaving The porous foam ceramic is similar to the ceramic blank in composition and has similar wettability. Under the action of sintering and infiltration, the foam ceramic cooperates with the bonding of glass powder to form a layer of tightly connected porous ceramic body on the surface of the ceramic blank to obtain a ceramic sheet with a porous surface. In the subsequent metallization process, the contact area between the foam ceramic and the metal slurry is greatly increased. The peel strength of the metallized layer after sintering can be greatly improved without relying on the composition of the metal slurry, thereby ensuring the vacuum sealing strength and airtightness of the metallized high-voltage DC relay ceramic. When it is prepared into a relay, its current carrying capacity is enhanced and more stable, thereby reducing losses.
[0066] S3: Preparation of metallization paste
[0067] S3.1: 1 part of aluminum oxide, 6 parts of molybdenum, 2 parts of manganese, 1 part of silicon oxide, 0.2 parts of lithium oxide, 2 parts of yttrium oxide powder and 4 parts of anhydrous ethanol are mixed and added into a planetary ball mill, and the ball milling speed is adjusted to 200 rpm. The ball milling is performed for 4 hours to obtain a mixture. The low-melting-point lithium oxide can promote the mutual migration of molybdenum and ceramic phases and improve the peeling strength of the metallization layer, while the high-melting-point yttrium oxide can fill the pores generated during the sintering process, making the metallization layer denser and improving the stability of the metallized high-voltage DC relay ceramic during sealing;
[0068] S3.2: The mixture is placed in an oven and dried at 80°C for 3 hours. After natural cooling, an adhesive is added. The adhesive is prepared by mixing ethyl cellulose and pinene alcohol in a mass ratio of 1:25. The mixture is mixed evenly to obtain a metallization paste.
[0069] S4: Roughening and metallization of porous ceramic sheets
[0070] S4.1: Immerse the ceramic sheet with a porous surface in a sodium hydroxide solution with a concentration of 1.2 mol / L, heat it in a constant temperature water bath at 55°C for 10 minutes, rinse it with distilled water 3 times, and then immerse it in an acid pickling solution, the components of which are: 120 mL / L sulfuric acid and 2 mol / L CrO3, heat it in a constant temperature water bath at 55°C for 60 minutes, take it out and rinse it with distilled water 3 times, clean and roughen the ceramic sheet with a porous surface, enhance the subsequent metallization paste infiltration effect on the roughened ceramic sheet during the sintering process, further enhance the peel strength of the metallization layer of the metallized high-voltage DC relay ceramic, and improve the stability of the metallized high-voltage DC relay ceramic to obtain a roughened ceramic sheet;
[0071] S4.2: Take 2 / 3 of the metallization paste and apply it evenly on the surface of the roughened ceramic sheet by screen printing, then place it in a vacuum sintering furnace and adjust the vacuum degree to 5×10 -3 Pa, sintered at 1600 °C for 2 hours to obtain a primary sintered ceramic sheet, the remaining metallization paste was evenly coated on the surface of the primary sintered ceramic sheet by screen printing, and then placed in a vacuum sintering furnace and the vacuum degree was adjusted to 5×10 -3 Pa, sintered at 900°C for 3 hours, and naturally cooled to room temperature to obtain a metallized high voltage DC relay ceramic.
[0072] Comparative Example 1:
[0073] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 is a metallized ceramic prepared by an activated molybdenum-manganese method, specifically, alumina ceramic is metallized with a Mo-Mn-Ti-Si-Al system paste;
[0074] The metallized high-voltage DC relay ceramics prepared in Example 1, Example 2, and Example 3 and Comparative Example 1 were respectively taken, and the peel strength of the metallized layer was measured using a Shimadzu tensile tester. The test was performed three times, and the data was recorded and tabulated, as shown in Table 1. It can be seen that the peel strength of the metallized high-voltage DC relay ceramics prepared in Example 1, Example 2, and Example 3 is higher than the peel strength of Comparative Example 1, which can prove that the embodiment prepares a metallized high-voltage DC relay ceramic in which the metallized layer and the ceramic are tightly combined;
[0075] .
[0076] Comparative Example 2:
[0077] Compared with Example 1, the difference of Comparative Example 2 is that step S1 is removed in Comparative Example 2, and the remaining steps are the same as those in Example 1;
[0078] Take comparative example 2, use Shimadzu tensile testing machine to measure the peel strength of its metallized layer, test three times, record the data and use the data of example 1 to make a table, as shown in Table 2, it can be seen that the peel strength of the metallized high-voltage DC relay ceramic metallized layer prepared in example 1 is higher than the peel strength of comparative example 1, which can prove that the example greatly improves the peel strength of the metallized layer after sintering by preparing a ceramic sheet with a porous surface;
[0079] .
[0080] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A metallization process for high voltage DC relay ceramics, characterized in that: The following steps are involved: S1: Preparation of alumina foaming slurry and impregnated sponge; S2: Preparation of ceramic sheets with porous surfaces; S3: Preparation of metallization paste; S4: Roughening and metallization of porous ceramic sheets; Step S1 specifically includes the following steps: S1.1: 18-20 parts of aluminum oxide, 0.4-0.5 parts of silicon oxide, 0.4-0.5 parts of magnesium oxide, 0.2-0.3 parts of calcium oxide and 0.3-0.4 parts of titanium oxide are placed in a ball mill of a planetary ball mill, 6-8 parts of anhydrous ethanol are added, the ball mill speed is adjusted to 260-280 rpm, and the ball mill is performed for 5-6 hours to obtain a ball milled material; S1.2: Take 2-3 parts of the ball-milled material and place them in a container, add 0.02-0.03 parts of carboxymethyl cellulose and 0.008-0.01 parts of polyacrylamide, then add 0.5-0.6 parts of glass powder and 0.3-0.4 parts of deionized water, stir to prepare an alumina foaming slurry, immerse a polyurethane sponge with a thickness of 0.5-0.6 cm in the alumina foaming slurry, stir to make it completely immersed, and obtain a slurry-impregnated sponge for standby use; Step S2 specifically includes the following steps: S2.1: Take 16-17 portions of the ball-milled material obtained in step S1.1, place them in a drying oven at 70-75°C for 2-3 hours, then place them in a grinder for grinding and granulation, and then press them into green bodies by cold isostatic pressing to obtain ceramic green bodies; S2.2: Remove excess slurry from the impregnated sponge by centrifugation and rolling, and then tightly wrap it on the surface of the ceramic blank and fix it to obtain a ceramic wrapped blank. Put the ceramic wrapped blank into an oven and dry it at a temperature of 80-85°C for 2-3 hours, then put it into a gas pressure sintering furnace, introduce nitrogen to make the pressure in the kettle reach 0.5-0.6MPa, heat it to 180-200°C at a heating rate of 5-6°C / min, then heat it to 600-650°C at a rate of 2-3°C / min, keep it warm for 50-55 minutes, and finally heat it to 1500-1600°C at a temperature of 10-12°C, keep it warm for 2-3 hours, and then naturally cool it to room temperature to obtain a ceramic sheet with a porous surface; Step S3 specifically includes the following steps: S3.1: 1-2 parts of aluminum oxide, 6-8 parts of molybdenum, 2-3 parts of manganese, 1-2 parts of silicon oxide, 0.2-0.3 parts of lithium oxide, 2-3 parts of yttrium oxide powder and 4-5 parts of anhydrous ethanol are mixed and added into a planetary ball mill, the ball milling speed is adjusted to 180-200 rpm, and the ball milling is performed for 3-4 hours to obtain a mixture; S3.2: drying the mixture in an oven at 75-80°C for 2-3 hours, adding an adhesive after natural cooling, and mixing well to obtain a metallized paste; Step S4 specifically includes the following steps: S4.1: Immerse the ceramic sheet with a porous surface in a sodium hydroxide solution with a concentration of 1.2-1.25 mol / L, heat it in a constant temperature water bath at 50-55°C for 8-10 minutes, rinse it with distilled water 2-3 times, and then immerse it in an acid washing solution, heat it in a constant temperature water bath at 50-55°C for 45-60 minutes, take it out and rinse it with distilled water 2-3 times to obtain a roughened ceramic sheet; S4.2: Take 1 / 2-2 / 3 of the metallization paste and apply it evenly on the surface of the roughened ceramic sheet by screen printing, then place it in a vacuum sintering furnace and adjust the vacuum degree to 1×10 -3 -5×10 -3 Pa, sintered at 1500-1600℃ for 1-2 hours to obtain a primary sintered ceramic sheet, the remaining metallization paste was evenly coated on the surface of the primary sintered ceramic sheet by silk screen printing, and then placed in a vacuum sintering furnace, and the vacuum degree was adjusted to 1×10 -3 -5×10 -3 Pa, sintered at a temperature of 800-900°C for 2-3 hours, and naturally cooled to room temperature to obtain a metallized high voltage DC relay ceramic.
2. The metallization process of a high voltage DC relay ceramic according to claim 1, characterized in that: The composition of the glass powder in step S1.2 and the mass fraction of each component are: SiO2: 98-99%, Al2O3: 0.5-1.5%, Fe2O3: 0.05-0.1%, CaO: 0.1-0.5%, MgO: 0.1-0.5%.
3. The metallization process of a high voltage DC relay ceramic according to claim 1, characterized in that: The pore number of the polyurethane sponge in step S1.2 is 45-50 ppi.
4. The metallization process of a high voltage DC relay ceramic according to claim 1, characterized in that: The particle size of the granulated material in step S2.1 is 10-15 μm.
5. The metallization process of a high voltage DC relay ceramic according to claim 1, characterized in that: The adhesive in step S3.2 is prepared by mixing ethyl cellulose and pinene alcohol in a mass ratio of 1:(25-28).
6. The metallization process of a high voltage DC relay ceramic according to claim 1, characterized in that: The composition of the pickling solution in step S4.1 is: 100 mL / L of sulfuric acid and 1.8 mol / L of CrO3.
Citation Information
Patent Citations
Gradient porous ceramic-metal composite connecting piece and preparation method thereof
CN115806444A